Politics of Resilience-Building: Explorations of Community-Based Interventions in Trinidad and Tobago - Pepin, Céleste; Esnard, Talia; Nicholson, Kimberly (The Canadian Journal of Action Research)

(untitled) (Canadian Association of Action Research in Education, 2025)
As climate change becomes a pressing issue, there are many concerns about the vulnerability and autonomy of small island developing states like the Caribbean, and relatedly, for the meaningfulness of the initiatives that are being designed and implemented to build community resilience. We use a decolonial framework and semi structured interviews with nine governmental and non-governmental community-based climate change actors in Trinidad and Tobago to explore the issues impacting community resilience. Thematic analyses point to community resilience constructions as bottom-up initiatives built on principles of participatory action, access, and co-creation of initiatives. Implications for community-based resilience are also addressed.